Geo year book : an overview of our changing environment 2006 - United Nations Environment Programme. Division of Early Warning and Assessment (Nairobi: United Nations Environment Programme, 2006)
Overview of major global and regional environmental issues and development that shaped policy decisions and actions during the course of the year; Emerging challenges--new findings presenting scientific progress made in the year that may assist society in recognizing and better understanding emerging environmental issues and help decision makers in designing adequate responses; GEO indicators highlighting some of the key global and regional environmental issues and trends that have been identified in GEO reports.
Includes bibliographical references.
Keywords: United Nations Environment Programme -- Periodicals; Environmental impact analysis -- Periodicals; Global environmental change -- Periodicals; Environmental policy -- Periodicals